Gagalnya Pluralisme? Kajian Historis dan Teologis Menuju Paradigma Baru Moderasi Beragama - Daud Manno (KHARISMATA: Jurnal Teologi Pantekosta, 2025)
This article examines the crisis of pluralism within the theological and historical framework of interfaith engagement. It traces the root causes of pluralism's shortcomings through a historical-theological lens and proposes religious moderation as a new paradigm that is more realistic and biblically grounded. Integrating theological, practical, and contextual approaches, this paper provides a foundation for a more discerning interreligious dialogue based on love, justice, and active societal participation. While pluralism offers inclusive values, it often fails to address the deep spiritual and sociological dynamics of religious communities. Religious moderation is not presented as a compromise of faith, but as a balanced approach that upholds theological fidelity while encouraging dialogical openness. The article highlights the importance of education, church involvement, and mission praxis oriented toward peace and reconciliation. By reimagining the role of theology in the midst of religious diversity, this work seeks to contribute both academically and practically to the development of a contextual, responsible, and peace-oriented interfaith engagement, particularly in pluralistic societies like Indonesia.Artikel ini membahas krisis pluralisme dalam konteks teologi dan sejarah interaksi antaragama. Penulis menelusuri akar kegagalan pluralisme melalui pendekatan historis dan teologis, lalu menawarkan moderasi beragama sebagai paradigma baru yang lebih realistis dan biblika. Dengan menggabungkan pendekatan teologis, praksis, dan kontekstual, artikel ini memberikan dasar bagi dialog lintas agama yang lebih bijaksana, berdasarkan kasih, keadilan, dan partisipasi aktif dalam masyarakat pluralistik. Gagasan utama yang diangkat adalah bahwa pluralisme, meskipun memiliki nilai inklusif, cenderung gagal menjawab realitas sosiologis dan spiritual umat beragama. Moderasi beragama diusulkan bukan sebagai bentuk kompromi iman, tetapi sebagai pendekatan yang menyeimbangkan antara kesetiaan teologis dan keterbukaan dialogis. Penulis juga menekankan pentingnya pendidikan, partisipasi gereja, dan misi Kristen yang berorientasi pada damai sejahtera sebagai wujud nyata dari paradigma moderasi tersebut. Dengan demikian, artikel ini bertujuan memberi kontribusi ilmiah dan praktis dalam merumuskan pendekatan yang kontekstual terhadap keragaman agama di Indonesia.